(untitled) (Islamic Sciences Journal, 2025)
The title of the research: [The Hadiths of the imperative verb in the book Sharh Mashariq al-Anwar by Muhammad ibn Mustafa Muslih al-Din al-Qawjawi, famously known as Shaykh Zadeh (d. 951 AH) (Study and Verification)]. Due to the importance of this commentary, which deals with the blessed Sunnah, we, the sons of this immortal nation and the descendants of these great ancestors, saw it as necessary for us to strive for what they strived for in order to complete their mission and preserve their works from extinction and loss after the occurrence of the many calamities that befell the Islamic world, which exceeded imagination in terms of apparent and hidden hatred and many conspiracies. For this reason, we sought to preserve one of the works of one of the great scholars. The reason for our choice of this commentary is that its author elaborated on the arts of Islamic jurisprudence and the various legal rulings, so he produced the commentary in an organized manner, and simplicity, ease, and refinement appeared in it in terms of composition, so it came with the diversity of issues and legal rulings that he spoke about. The research plan for this study consists of an introduction and two main sections. The first section focuses on the author and contains two subsections: Subsection 1: The author’s biography. Subsection 2: The author’s academic background. The second section focuses on the work itself and also contains two subsections: Subsection 1: A description of the manuscript, its methodology, and its significance. Subsection 2: An analysis of the edited text.